Assessment for treatment options at the Young Dong Coal Mine site, South Korea - Ranville, J.F.; Sibrell, P.L.; Wildeman, T.R.; Lee, B.T.; Jang, M.; Shim, Y.S.; Ji, W.H.; Park, H.S.; Lee, H.J. (2009)
The Young Dong Coal Mine site in northeastern South Korea was closed in the early 1990s and initial reclamation was finished in 1995. Even though the adit was filled with limestone, there is still significant acid rock drainage (ARD) flowing from the site. An assessment that was started in March 2008 revealed that there were three types of water flowing from various sources on the site. ARD still flowed from the adit; which carried an average of 500 mg CaCO 3 / L of mineral acidity primarily in the form of Fe(II) with a flow that reached 2.8 m3 / min in spring runoff. This water is the focus of this paper. The hydrology is complex because there are at least two periods of high surface flow during the year, one in the spring and one during monsoon season. The water issuing from the adit is from a diffuse aquifer where concentrations increase when flow increases. In addition, the terrain is quite steep with few level spots. One other factor in the assessment of treatment is that a limestone quarry is only a few kilometers from the site. All of these factors have led to the conclusion that none of the traditional methods of passive treatment can be applied to this site. Instead, it is proposed to use an upgrade of a diversion well that is called a pulsed passive limestone reactor (PPLR). With maximizing all of the parameters that can be changed on a PPLR, it is anticipated that a one stage PPLR system could generate up to 250 mg CaCO 3 / L and so there would be a set of reactors needed to treat the complete flow.